The Effect of Green Accounting, Tax Aggressiveness, and Company Size on Firm Value - Naibaho, Novselyn; Hutabarat, Francis; Siregar, Lorina (Universitas Ibn Khladun Bogor, 2024)
This study aims to provide empirical evidence regarding the influence of green accounting, tax aggressiveness, and firm size on firm value in the Investor33 companies listed on the Indonesia Stock Exchange during the period 2019-2022. This research employs descriptive statistical analysis and panel data regression analysis using Eviews 11. Data for the study are sourced from the Investor33 Index companies from 2019 to 2020, obtained from www.investing.com and the official websites of the companies, resulting in 132 samples. The analysis utilizes linear regression analysis based on the selection between fixed effect model, random effect model, and common effect model, with reference to the results of the Chow test and the Hausman test. The findings reveal a positive and significant influence of green accounting on firm value among companies in the Investor33 Index. Conversely, no significant influence is found between tax aggressiveness and firm value, as well as between firm size and firm value in this study.